Values and ethics in counselling and psychotherapy - Proctor, Gillian, 1969- 4 0 16; 5 (Los Angeles : SAGE Publications, 2014)
This book offers an introduction to values and ethics in counselling and psychotherapy, helping you to develop the ethical awareness needed throughout the counselling process. The book covers: Context and emergence of ethics in counselling ; Exercises to explore personal and professional values ; Tools to develop ethical mindfulness ; Differences between therapeutic models ; Relational ethics ; Ethical dilemmas and issues ; Practice issues including confidentiality, boundaries and autonomy versus beneficence. Using in-depth case studies of counselling students, the author demonstrates the constant relevance of values and ethics to counselling and psychotherapy, equipping trainees with the tools to successfully navigate values and ethics in their professional practice.
What are your personal values? -- How are values relevant to therapy? -- Ethics in healthcare -- Ethics in counselling and psychotherapy -- Making ethical decisions -- Couselling, psychotherapy and society -- Ethical mindfulness -- Values and ethics in models of therapy -- Autonomy versus beneficence -- Confidentiality -- Boundaries -- Particular boundary issues.
Includes bibliographical references (pages [230]-241) and index.
Keywords: 2 -- 0; 6; Moral and ethical aspects.;Moral and ethical aspects. -- Counseling;Psychotherapy -- 20; 20; 2